Traditional Chinese and Indian medicine in the treatment of opioid-dependence: a review - Fatemeh Doosti; Saeedeh Dashti; Seyed Meghdad Tabatabai; Hossein Hosseinzadeh (Mashhad University of Medical Sciences, 2013)
Objective: In this study, the current literatures on the use of herbs and herbal preparations of Traditional Chinese and Indian Medicine for the treatment of opioid addiction were reviewed. Methods: Search was done in databases such as Pub Med, Science Direct, Scopus, Springer Link, and Google Scholar. Results: Among 18 retrieved studies, 3 studies were about asafetida extract, an approved preparation for ameliorating drug abstinence in China. Chinese preparations including Composite Dong Yuan Gao, Qingjunyin and TJ-97 (a water extract of dai-bofu-to) as well as Indian ones, Mentate and Shilajit, were reported to have positive effects against opioid withdrawal, dependence, and tolerance. Moreover, Levo-tetrahydropalmatine and L-Stepholidine, in addition to extracts of Caulis Sinomenii and Sinomenium acutum showed similar effects. Banxia Houpu Decoction, Fu-Yuan pellet, Jinniu capsules, Qingjunyin, Tai-Kang-Ning capsule, and Xuan Xia Qudu Jiaonang (WeiniCom) from Chinese preparations, showed anti-addiction effects in randomized, double-blind and, in some studies, multicenter clinical trials. Conclusion: Traditional herbal preparations of China and India have anti-addiction effects with less adverse effects than alpha2-adrenergic or opioid agonists.